EFEKTIVITAS PENGELOLAAN KURIKULUM OPERASIONAL (STUDI KOMPARASI SDIT AT-TAUBAH BATAM DAN SD MUHAMMADIYAH PLUS BATAM) - Kasmawati; Sholehuddin (STKIP Subang, 2026)
This study analyzes the effectiveness of operational curriculum management at SDIT At-Taubah Batam and SD Muhammadiyah Plus Batam and compares its impact on the achievement of educational goals. Using a qualitative approach with a comparative study method, data were collected through in-depth interviews, participatory observation, and documentation studies. The results showed that SDIT At-Taubah Batam excels in program diversity but is hindered by the standardization of tahfidz methods, educator qualifications, and documentation. SD Muhammadiyah Plus Batam excels in program structuring, differentiated instruction, and measurable memorization achievement. The study concludes that the effectiveness of curriculum management is determined by methodological consistency, teacher competence, and support systems. Recommendations include method standardization, improvement of teacher competence, and optimization of program evaluation.